The Influence of Love of Money, Morality, and the Whistleblowing System on the Tendency of Accounting Fraud - Ni Wayan Angellin; Ni Ketut Rasmini (E-Jurnal Akuntansi, 2025)
The tendency for accounting fraud is an unlawful act that can harm the organization. To avoid accounting fraud, organizations need to pay attention to the factors that influence the tendency of accounting fraud. The purpose of this research is to determine the influence of love of money, morality, and the whistleblowing system on the tendency for accounting fraud. This research was conducted at the Village Credit Institution in Gianyar Regency with respondents, two supervisory bodies, the chairman, and one staff member, namely the cashier. The number of samples used was 292 people, using the proportationate stratified random sampling method. Data collection was carried out using a questionnaire analyzed with SEM PLS4.0. The results of this research show that love of money has a positive effect on the tendency for accounting fraud, while morality and the whistleblowing system have a negative effect on the tendency of accounting fraud. This means that a person's high love of money can increase fraud, whereas high levels of morality and the implementation of a good reporting system can minimize the tendency for accounting fraud to occur in LPD financial management.